2014
DOI: 10.5657/fas.2014.0403
|View full text |Cite
|
Sign up to set email alerts
|

Development of Reaction Flavors with Enzymatic Hydrolysate of Krill Euphausia superba in Ramen Sauce

Abstract: Antarctic krill Euphausia superba is an excellent potential source of food protein. We used enzymatic hydrolysate of Antarctic krill and 10 other precursors to seek the optimum krill reaction flavor and apply to ramen sauce. Krill concentrate and powder were compared by sensory evaluation. The krill powder performed better preference, and was added to ramen sauce, which itself performed better than a commercial shrimp flavored sauce. In total, 47 and 39 volatile compounds were identified from krill concentrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The odorants with the highest FDs in the eHMP sample were determined to be 3-(methylsulfanyl)propanal (11,FD 256), 2-and 3-methylbutanoic acids (20, FD 256), 2-acetylthiazole (18, FD 64), 2-phenylacetaldehyde (19,FD 64), HDMF (28,FD 64), sotolon (31, FD 64), 2aminoacetophenone (32, FD 64), and 4-hydroxy-3-methoxybenzaldehyde (36, FD 64) (Table 1). Consistent with the literature, 2-acetyl-1-pyrroline (5,FD 16), butanoic acid (16,FD 16), 2-acetyl-2-thiazoline (23,FD 16), phenylacetic acid (35, FD 16), 1-octen-3-one (4, FD 4), acetic acid (10, FD 4), and 2,3-diethyl-5-methylpyrazine (13, FD 4) were previously detected in cooked mushrooms. 2 The odorants with the highest FDs in the eHMP + cys sample were determined to be 3-(methylsulfanyl)propanal (11,FD 256), 2-and 3-methylbutanoic acids (20,FD 256), sotolon (31, FD 256), 2-furfurylthiol (9, FD 64), p-cresol (29, FD 64), 2-aminoacetophenone (32, FD 64), indole (34, FD 64), phenylacetic acid (35, FD 64), and 4-hydroxy-3-methoxybenzaldehyde (36, FD 64).…”
Section: ■ Results and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The odorants with the highest FDs in the eHMP sample were determined to be 3-(methylsulfanyl)propanal (11,FD 256), 2-and 3-methylbutanoic acids (20, FD 256), 2-acetylthiazole (18, FD 64), 2-phenylacetaldehyde (19,FD 64), HDMF (28,FD 64), sotolon (31, FD 64), 2aminoacetophenone (32, FD 64), and 4-hydroxy-3-methoxybenzaldehyde (36, FD 64) (Table 1). Consistent with the literature, 2-acetyl-1-pyrroline (5,FD 16), butanoic acid (16,FD 16), 2-acetyl-2-thiazoline (23,FD 16), phenylacetic acid (35, FD 16), 1-octen-3-one (4, FD 4), acetic acid (10, FD 4), and 2,3-diethyl-5-methylpyrazine (13, FD 4) were previously detected in cooked mushrooms. 2 The odorants with the highest FDs in the eHMP + cys sample were determined to be 3-(methylsulfanyl)propanal (11,FD 256), 2-and 3-methylbutanoic acids (20,FD 256), sotolon (31, FD 256), 2-furfurylthiol (9, FD 64), p-cresol (29, FD 64), 2-aminoacetophenone (32, FD 64), indole (34, FD 64), phenylacetic acid (35, FD 64), and 4-hydroxy-3-methoxybenzaldehyde (36, FD 64).…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…Previous studies have shown that protein hydrolysates could enhance the perceived saltiness and overall flavor of foods. 5 Accordingly, thermally treated mushroom hydrolysates (with and without the addition of cysteine) were generated and screened for the enhancement of saltiness perception in a sensory study. Results showed that the eHMP sample had a higher saltiness rating than the control sample (broth alone).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on krill edibility has progressed in many countries including Russia, where research began in 1961. Poland, Japan, Chile, and China have studied krill and their use (Kim, 2011). Further research is still required for their use as ingredients in food products.…”
Section: Introductionmentioning
confidence: 99%
“…The fish odor is a sensory quality factor for fish. Therefore, krill are immediately treated by rapid freezing after fishing in most pelagic fishing vessels to preserve their freshness (Kim, 2011).…”
Section: Introductionmentioning
confidence: 99%